1992
DOI: 10.1093/oxfordjournals.jbchem.a123958
|View full text |Cite
|
Sign up to set email alerts
|

Gene Structure and Multiple mRNA Species of Drosophila melanogaster Aldolase Generating Three Isozymes with Different Enzymatic Properties1

Abstract: Genomic clones encoding the Drosophila aldolase gene were isolated and the organization of the gene was determined. The protein-coding region spanning nearly 3.5 kb consists of five coding exons (exon 2, 3, 4 alpha, 4 beta, and 4 gamma). The insect exon 2 corresponds to exons 2 to 7 of vertebrate aldolase genes and thus appears to have been formed by the fusion of these 6 exons into a single exon during evolution. The Drosophila aldolase gene is predicted to generate mRNAs for three isozymes (alpha-, beta-, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In invertebrates, the presence of more than one aldolase isozyme has also been described. In D. melanogaster there are three isozymic forms of aldolase which are generated from a single gene by alternative splicing (Kai et al, 1992). C. elegans and Clonorchis sinensis present two and three isozymes, respectively (Cho et al, 2006;Inoue et al, 1997), and similarly to vertebrates, each of these isozymes is encoded by different genes.…”
Section: Discussionmentioning
confidence: 99%
“…In invertebrates, the presence of more than one aldolase isozyme has also been described. In D. melanogaster there are three isozymic forms of aldolase which are generated from a single gene by alternative splicing (Kai et al, 1992). C. elegans and Clonorchis sinensis present two and three isozymes, respectively (Cho et al, 2006;Inoue et al, 1997), and similarly to vertebrates, each of these isozymes is encoded by different genes.…”
Section: Discussionmentioning
confidence: 99%
“…The production of heterogeneity in the amino acid sequences by alternative splicing is well documented in animal systems leading to proteins which are development-and tissue-specific [22]. Recently, in Drosophila, it has been reported that three mRNA species encoding aldolase isozymes are generated through one of the three 3'-terminal exons including one genomic gene [23]. In higher plants, the two isozymes of spinach ribulosebisphosphate carboxylase/oxygenase activase have arisen from alternative splicing of a common pre-mRNA, in which the mRNAs near the 3'-end of the coding region differed by the presence or absence of the 22-bp sequence [24].…”
mentioning
confidence: 99%
“…Vertebrates and invertebrates possess three FBP aldolase isoenzymes (Shiokawa et al 2002). The presence of these three isoenzymes in C. sinensis seems acceptable when it is considered that Drosophila melanogaster (Kai et al 1992) and Caenorhabditis elegans (Inoue et al 1997) possess more than two FBP aldolase isoenzymes.…”
Section: Discussionmentioning
confidence: 99%
“…A lysine residue (K229) forming a putative Shiff base is represented by a bold character on a black background. The aldolase isozymes are as follows: human aldolase A (P04075, Sakakibara et al 1985), Xenopus laevis A (BAA19524, Hikasa et al 1997), lamprey muscle type (M) (P53445, Zhang et al 1995), Drosophila melanogaster Dm a (JX0233, Kai et al 1992), Caenorhabditis elegans Ce-1 (P54216, Inoue et al 1997), Onchocerca volvulus (AAD38430, McCarthy et al 2002), E. multilocularis (CAC18550, Brehm et al 2000), and S. mansoni (AAA57567, El-Dabaa et al 1998) of C. sinensis FBP aldolases, a lysine residue is positioned at the 6-phosphate binding site and a histidine residue is located at 361 (CsFbA-1) and 362 (CsFbA-2 and -3), suggesting that these three putative isoenzymes could be assigned as FBP aldolase type A enzymes. In this study, a large number of ESTs was collected from C. sinensis and an EST platform was formulated as an aid to future research at the multigene level.…”
Section: Discussionmentioning
confidence: 99%